Trp53 loss drives the neoplastic transformation of Pik3caH1047R-induced vascular malformation in a mouse model - Miaolu Tang; Jessica Sallavanti; Matthew Lanza; Danielle Covington; Wei Li (PLoS ONE, 2026)
Vascular malformations are anomalies of blood or lymphatic vessels that are frequently associated with activating PIK3CA mutations. Although these lesions are generally considered non-neoplastic, rare cases of malignant transformation to angiosarcoma have been reported, and the mechanisms underlying this progression remain unclear. Here, using a conditional mouse model in which GFAP-Cre ERT2 induces Pik3ca H1047R expression with or without Trp53 loss, we observed an unexpected cutaneous vascular phenotype rather than intracranial tumor formation. Following tamoxifen induction, blood blister-like lesions developed on the tail, ear, and paw in 86.9% (53/61) of mice harboring at least one Pik3ca H1047R allele, whereas no lesions were observed in mice lacking the mutant allele (0/13, P < 0.0001). Trp53 loss did not significantly alter lesion incidence (76.5% vs 70.2%, P = 0.76), indicating that PIK3CA activation is sufficient for lesion initiation. Histologically, the lesions consisted of cavernous CD31 + vascular channels with frequent thrombosis, most prominently in the dermis, consistent with venous or arteriovenous malformations. Mechanistically, endothelial cells lining the lesions showed little detectable p-AKT signal, whereas adjacent intervascular cells displayed increased p-AKT and focal GFAP expression, suggesting that PI3K activation in non-endothelial intervascular cells contributes to lesion initiation and remodeling. Importantly, Trp53 deficiency promoted malignant-like progression, with lesions exhibiting endothelial atypia, mitotic activity, intraluminal tufting, and infiltrative growth; 7 of 159 tail lesions showed malignant-like features reminiscent of angiosarcoma. Together, these findings demonstrate that PIK3CA activation initiates highly penetrant vascular malformations, whereas p53 loss promotes their rare neoplastic transformation. This model provides mechanistic and translational insight into how benign PIK3CA -mutant vascular malformations may progress toward vascular malignancy and offers a platform for studying biomarkers and therapeutic strategies to prevent this transition.